Productivity and Responsiveness of Tax Yields in Nepal (NUTA Journal, 2018)
This study is based on secondary data published by the government of Nepal covering a period between 1990/91 and 2013/14 fiscal year. The various sources of revenue as a proportion of the GDP have been analyzed during this period. An adjusted revenue series have been prepared for total and the individual taxes by using the Sahota method of proportional adjustment. The Productivity and Responsiveness of taxes has been measured by estimating the elasticity and buoyancy co-efficient using double log linear regression equation. The findings reveal that indirect tax has been playing a dominant role for total tax revenue collection. Indirect tax is considered regressive in nature and is not justifiable on equity ground and progressiveness. Regarding elasticity and buoyancy, the elasticity coefficient of overall taxes are less than unity and it is inelastic in nature. But, buoyancy coefficient of overall taxes is greater than unity. This high buoyancy but low elasticity of all major tax heads signifies the need for additional government efforts of expanding the tax base to increase revenue and lower its resource gap.